Long-term tracking and population characteristics of lipoprotein (a) in the Cardiovascular Risk in Young Finns Study - Raitakari Olli; Kivelä Annukka; Pahkala Katja; Rovio Suvi; Mykkänen Juha; Ahola-Olli Ari; Loo Britt-Marie; Lyytikäinen Leo-Pekka; Lehtimäki Terho; Kähönen Mika; Juonala Markus; Rönnemaa Tapani; et al. (Elsevier Ireland Ltd, 2022)
Background and aims
Lipoprotein (a) (Lp(a)) is a causal risk factor for cardiovascular diseases and its levels are under strict genetic control. Therefore, it is hypothesized that the concentration of Lp(a) remains stable throughout life. Finns have lower Lp(a) levels than central Europeans, but it is unknown whether there are differences within Finland, especially between the eastern and western parts of the country with known genetic duality and persistent differences in cardiovascular disease rates. We have examined the long-term stability of Lp(a) levels over 25 years in the Cardiovascular Risk in Young Finns Study (YFS), and the characteristics of individuals with different Lp(a) levels, including their geographical origin within Finland.
Methods
In YFS, the first large baseline examination was conducted in 1980 (baseline age, 3–18 years). Several follow-ups during the past 40 years have been conducted to investigate the determinants of cardiometabolic health. Lp(a) levels have been measured in study years 1986 (N = 2464, ages 9–24 years), 2001 (N = 2281, ages 24–39 years), 2007 (N = 2204, ages 35–45 years) and 2011 (N = 2044, ages 39–49 years). Tracking of Lp(a) was estimated by calculating Spearman's rank order correlations between the study years, and by cross-tabulating how many individuals diagnosed with either elevated or non-elevated Lp(a) levels in 1986, 2001 and 2007 remained in the same category in the latest follow-up in 2011.
Results
Spearman's correlation coefficients varied between r = 0.84–0.96. Most individuals (87–94%) who had a high Lp(a) level (>30 mg/dl) in any of the previous study years had a high level also in 2011. On average, the median Lp(a) levels were consistently ∼20% higher in the individuals originating from eastern Finland compared to those from western Finland, but there were no differences in the distribution of known genetic determinants between eastern and western Finns that would have explained the observed difference.
Conclusions
These data confirm that Lp(a) levels remain very stable over the life-course. In line with the genetic duality between eastern and western parts of Finland, we observed about 20% higher Lp(a) levels in individuals originating from eastern Finland compared to those originating from western Finland.